Evidence of microcystin bioaccumulation and its effects on structural alterations in various shrimp (Litopenaeus vannamei Boone, 1931) tissues from shrimp aquaculture in the northern coastal region of East Java, Indonesia - Soegianto, Agoes; Mukholladun, Wildanun; Putranto, Trisnadi Widyaleksono Catur; Marchellina, Ary; Manaf, Latifah Binti Abd; Irnidayanti, Yulia; Hartl, Mark G.J.; Payus, Carolyn Melissa (Elsevier Ltd, 2025)
Microcystins are generated by diverse cyanobacteria in shrimp ponds marked by high nutrient levels. The study examined microcystin-leucine arginine (MC-LR) in the pond water, gills, hepatopancreas, and muscle of shrimp (Litopenaeus vannamei) from shrimp ponds on the northern coast of East Java and its effects on their histological structures. In shrimp ponds dominated by cyanobacteria particularly Microcystis and Oscillatoria, MC-LR levels were high. In pond water, Microcystis and Oscillatoria levels increased along with NO2−, NH4+, clarity, and salinity. Shrimp tissues, such as the gills and hepatopancreas, experienced elevated MC-LR concentrations as a consequence of the MC-LR toxin increase in pond water. Shrimp inhabitants of ponds with elevated MC-LR concentrations exhibited significant changes in histological architecture, like hyperplasia in gill tissue and extensive vacuolation in hepatopancreas tissue. L. vannamei muscle samples show MC-LR amounts below the WHO's recommended daily intake of 0.04 μg/kg body weight/day, indicating no health risks to humans.